One-pot supercritical water synthesis of Bi2MoO6-RGO 2D heterostructure as anodes for Li-ion batteries. Issue 7 (1st April 2021) - Shetty, Manjunath; Schüßler, Christian; Shastri, Mahesh; Sabbanahalli, Chethan; Chitrabhanu, C.P.; Murthy, M.; Jagadeesh Babu, S.; Tomai, Takaaki; Anantharaju, K.S.; Shivaramu, Prasanna D.; Rangappa, Dinesh
Abstract: Two dimensional (2D) materials stacked with Van der waals bonding to obtain a heterostructure have always generated tailored physical and chemical properties. In this paper, the development and application of single-phase 2D Bi2 MoO6 -reduced graphene oxide (BMO-RGO) heterostructure by one-pot supercritical water (SCW) method is reported for the first time. The as-synthesized nanocomposite of BMO-RGO with single-phase orthorhombic crystal structure is confirmed by XRD. The 2D nanoflake morphology was observed under transmission electron microscopy (TEM). X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Fourier transform infrared spectroscopy is performed to confirm the presence of BMO-RGO, RGO, and other functional groups, respectively. The specific capacities obtained through charge-discharge measurements from BMO and BMO-RGO heterostructure nanocomposites are compared and the optimization of RGO wt% is established. After 50 cycles, the capacity retention is around 202 mA h g −1 for BMO with 24 wt% RGO (BMO-24RGO) nanocomposite. This value is higher in comparison to pure BMO nanoflakes which have a capacity retention of 25 mA h g −1 . These results show the influence of RGO content on the performance of electrochemical measurements when compared to pure BMO and BMO-24RGO electrodes. One-pot SCW synthesis is found to be a reliable method for the synthesis of BMO-RGO nanocomposite.